LGG-06. Selumetinib in pediatric patients with non-neurofibromatosis type 1-associated, non-optic pathway (OPG) and non-pilocytic recurrent/progressive low-grade glioma harboring BRAFV600E mutation or BRAF-KIAA1549 fusion: a multicenter prospective Pediatric Brain Tumor Consortium (PBTC) Phase 2 trial. (3rd June 2022) - Fangusaro, Jason; Onar-Thomas, Arzu; Poussaint, Tina Young; Lensing, Shelly; Wu, Shengjie; Ligon, Azra H; Lindeman, Neal; Stewart, Clinton F; Jones, David T W; Pfister, Stefan M; Smiley, Natasha Pillay; Leach, James; et al.
Abstract: BACKGROUND: A greater understanding of the Ras-MAP kinase pathway in pediatric low-grade glioma (LGG) paired with the availability of selective inhibitors has enhanced the ability to target this pathway with therapeutic intent. METHODS: The PBTC conducted a multi-institutional phase II study (NCT01089101) evaluating selumetinib (AZD6244, ARRY-142886), a MEK I/II inhibitor, in children with recurrent/progressive LGG assigned to 6 strata and treated at a dose of 25 mg/m2/dose PO BID for up to two years. Here we present stratum 5 which enrolled children without NF1, non-OPG and non-pilocytic LGG harboring either a BRAFV600E mutation or BRAF-KIAA1549 fusion. RESULTS: Twenty-four of 25 children enrolled were eligible; 23 were evaluable for the primary radiologic response endpoint. Enrollment stopped early due to slow accrual and initiation of COG ACNS1931. The most common histologies were ganglioglioma (42%) and astrocytoma NOS (33%). Thirteen tumors (54%) had BRAF-KIAA1549 fusion; 11 (46%) had the BRAFV600E mutation. Five of 23 (22%) evaluable patients achieved a centrally confirmed partial response (PR), 12 (52%) had stable disease and 6 (26%) had progression with a 2-year progression-free survival of 75 + 9%. Four of 11 (36%) patients with a BRAFV600E mutation and 1/12 (8%) with a BRAF-KIAA1549 fusion achieved a PR. The 2-year PFS did not significantly differ between tumors with BRAFV600E mutation (82 + 12%) versus BRAF-KIAA1549 fusion (68 + 13%) (n=24, p=0.548). No patient remains on therapy. The most common attributable toxicities were grade 1/2 ALT/AST elevation, dry skin and leukopenia. Rare grade 3/4 toxicities included elevated CPK, rash, paronychia, fever, weight gain and sinus tachycardia. CONCLUSIONS: Despite lower than planned accrual, selumetinib met the design threshold for success in treating children with recurrent/progressive non-pilocytic, non-OPG LGG without NF1 that harbored the common BRAF aberrations. Ongoing phase 3 prospective studies will better determine the role of this agent in this population.